Skilled Immigration and Firm-Level Upgrading as Exports Boosters in a Developing Country - Carlo Lombardo; Leonardo Pe\~naloza-Pacheco (CESifo GmbH, 2025)
We examine firm-level upgrading in Colombian manufacturing firms as a result of a high-skilled labor supply shock triggered by the Venezuelan exodus. Using a unique and confidential dataset from 2013 to 2019 and a shift-share instrumental variables approach, we find that the increased supply of skilled workers primarily drove high-skill hires, especially in R&D divisions. This skill-upgrading process boosted investments in R&D activities. Improved access to higher-quality inputs led to better production and organizational processes, product enhancements, and an increased likelihood of obtaining quality certifications, which serve as a straightforward objective measure of firm-level upgrading. Collectively, these changes were crucial for firms to increase their exports at both the extensive and intensive margins. This effect was driven by a rise in differentiated product exports, allowing firms to enter new and more sophisticated markets, particularly in high- and upper-middle-income countries.
Keywords: D22; D24; F22; F14; F16; J61; L16; O14; O31; 330; firm-level upgrading; migration; trade; development